2018
DOI: 10.18203/2320-6012.ijrms20182457
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of intraocular pressure in myopia and hyperopia among a Nigerian population just diagnosed with primary open angle glaucoma in Benin City

Abstract: Background: Increasing evidence suggests that high myopia is salient in the pathologic process of POAG, and IOP (Primary Open Angle Glaucoma (POAG), and Intra-ocular Pressure (IOP)) remains the crucial risk factor for this condition. Still, some other studies have signified that glaucoma was diagnosed in myopes independent of IOP, suggesting that predisposition to glaucoma in myopes may not be dependent on mechanisms related to high pressures.The aim of this study was therefore to compare the intraocular press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This implies that as myopia increases, the intraocular pressure also increases. This is consistent with findings by Osaiyuwu et al [11] and Megwas et al [22] Tham et al [24] in Singapore, Sowjanya et al [25] in India and Jin et al [26] in Korea also obtained similar findings. However, Chinawa et al reported no correlation between myopia and intraocular pressure [27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This implies that as myopia increases, the intraocular pressure also increases. This is consistent with findings by Osaiyuwu et al [11] and Megwas et al [22] Tham et al [24] in Singapore, Sowjanya et al [25] in India and Jin et al [26] in Korea also obtained similar findings. However, Chinawa et al reported no correlation between myopia and intraocular pressure [27].…”
Section: Discussionsupporting
confidence: 92%
“…An association between refractive error and intraocular pressure has been reported among children and adults [9,10]. Increasing levels of intraocular pressure has been found in individuals with myopia as opposed to those with emmetropia or hypermetropia [4,11]. Myopic eyes have been shown to have higher intraocular pressures than non-myopic eyes and it has been hypothesised that a higher intraocular pressure may affect the development of myopia in children [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was also supported by Osaiyuwu et al . [ 52 ] Theories surrounding the interaction between increasing degrees of myopia and intraocular pressure have been inconclusive. It was suggested that increasing levels of intraocular pressure results in gradual stretching of the eyeball leading to myopia[ 53 ] while others suggested that increase in scleral tension within the lamina cribosa results in increased susceptibility to damage in myopes even when the intraocular pressure is normal.…”
Section: Discussionmentioning
confidence: 99%
“…highly consistent with the present study. Osaiyuwu et al, 24 analyzed the Nigerian population and demonstrated that myopes had higher mean IOP compared to hypermetropic. They added that the myopes had more incidence of POAG that was associated with IOP in a Nigerian population.…”
Section: Discussionmentioning
confidence: 99%